Prospective study of clinical, radiological and functional outcome of anterior bridge plating for shaft of humerus fracture - Kumar, Abhishek; Bade, Rahul (International Journal of Research in Orthopaedics, 2020)
Background: Shaft of humerus (SOH) fracture has been conventionally treated with either open reduction internal fixation with plate osteosynthesis or immobilization as conservative treatment. Intramedullary interlocking nailing (IMIL) and anterior bridge plating (ABP) are both newer modalities of internal fixation for SOH fracture. Rotator cuff irritation is a known complication of IMIL nailing of the humerus. Here, we present clinical, radiological, and functional outcome of SOH fracture fixation by ABP using a minimally invasive method. Methods: Thirty patients with SOH fracture were treated surgically via an anterior minimally invasive plate osteosynthesis (MIPO) approach with ABP. There were 21 male and 9 female patients, and the average age was 38.6±10.45 years. The mechanism of injury was road traffic accidents (60%) and ground level fall (40%). Functional assessments were obtained with University of California at Los Angeles (UCLA) score and mayo elbow performance index (MEPI) during the follow-up period. Results: At the end of 6 months follow-up, 29 (96.7%) patients had excellent to good UCLA and MEPI scores. Varus/valgus angulation was reported in 4 (13.3%) patients. Two patients (6.7%) had radial nerve neuropraxia and delayed union, while 1 (3.3%) patient had screw back-out or loosening. The mean duration of radiation exposure was 178±41.2 seconds. ABP for SOH fractures is a safe and effective treatment modality. Conclusions: This treatment protocol produces high rates of union, excellent functional recovery, and minimal biological disruption.